1996
DOI: 10.1111/j.1365-2885.1996.tb00018.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of level of feed intake on the pharmacokinetic disposition and efficacy of ivermectin in sheep

Abstract: The kinetic disposition of orally administered [3H]-Ivermectin (IVM) was examined in sheep in which the feed intake was maintained at either 800 or 400 g/day. The [3H]-metabolites were almost completely associated with particulate digesta in the rumen. In the low feed intake group the digesta flow was slower than in sheep on high feed intake. This resulted in an extended residence time and greater availability of IVM and its metabolites. The anthelmintic efficacy of IVM was then examined in sheep in which feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Thus, drug efficacy can be improved by enhancing the concentration of MLs in the plasma and target tissues. Different physiological and pharmacological methods have been used to increase the systemic bioavailability of MLs, such as food restriction in sheep (Ali and Hennessy 1996), fasting in horses (Alvinerie et al 2000) and drug interference (Dupuy et al 2003). The possible involvement of the lymphatic route in the intestinal absorption of moxidectin led us to study the influence of lipid ingestion on the pharmacokinetic parameters of orally administered moxidectin.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, drug efficacy can be improved by enhancing the concentration of MLs in the plasma and target tissues. Different physiological and pharmacological methods have been used to increase the systemic bioavailability of MLs, such as food restriction in sheep (Ali and Hennessy 1996), fasting in horses (Alvinerie et al 2000) and drug interference (Dupuy et al 2003). The possible involvement of the lymphatic route in the intestinal absorption of moxidectin led us to study the influence of lipid ingestion on the pharmacokinetic parameters of orally administered moxidectin.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation, however, is difficult to conciliate with our results, since the unabsorbed fraction of ingested ivermectin was fully recovered in the faeces of the lickers. Moreover, several studies argue for the stability of ivermectin in rumen fluids in cattle and sheep [3,6] and show that there is rather an extensive adsorption of ivermectin to the digesta particulates of the rumen [1]. Our model stipulates that the fraction of drug which is not absorbed in compartment GIT 1 will not be absorbed later in compartment GIT 2.…”
Section: Discussionmentioning
confidence: 99%
“…By seven days, the faecal residues account for 69% of the dose and 61-69% of these residues are present as the parent drug [40,76]. Other studies have shown 95% recovery of the total dose in the faeces of sheep seven days after intra-ruminal administration [2], two-thirds of this being recovered during the first two days [98]. The presence of ivermectin residues in sheep droppings after oral administration influenced the survival of fly and beetle larvae for less than a week after treatment, but such transient effects were unlikely to have a major impact on insect populations [113].…”
Section: Concentration Stability and Activity Of Anthelmintics In Thmentioning
confidence: 89%